Video display terminal use during pregnancy and reproductive outcome--a meta-analysis. - Parazzini, F; Luchini, L; La Vecchia, C; Crosignani, P G (Journal of Epidemiology & Community Health, 1993)
The aim was to obtain quantitative information from published data on the potential association between video display terminal (VDT) use during pregnancy and the outcome. Results of nine published case-control studies (or cohort studies analysed as case-control) on the relation between VDT exposure during pregnancy and the outcome were sought by reviewing reference lists in relevant reports and by conducting manual and computer searches of the reports published in English. The nine reviewed reports included information on about 9000 cases of spontaneous miscarriages, 1500 of low birth weight, 2000 of congenital malformation, and 50,000 controls. The results of these studies on each outcome of pregnancy examined were reduced to a single 2 x 2 table (cases/controls--exposed/unexposed). Pooled odds ratio (OR) estimates were computed separately for miscarriage, low birth weight, and congenital malformation. Seven studies analysed the relation between VDT exposure in pregnancy and the risk of miscarriage: the estimates' crude OR of spontaneous abortion ranged from 0.9-1.2 and the pooled OR was 1.0 (95% confidence interval (CI) 0.9, 1.0). No consistent evidence of increasing risk with duration of exposure to VDT was found. Two studies analysed the relation between VDT use and risk of having a low birth weight infant: the OR estimates in the individual studies were 1.0 and 1.1. Likewise, no relation emerged from the five studies providing information on congenital malformations and VDT use: the pooled OR was 1.0 (95% CI 0.9, 1.2). No specific malformation pattern emerged. This meta-analysis provides reassuring evidence on the absence of any major risk of adverse pregnancy outcome as a result of exposure to a VDT. With the number of cases reviewed, it was possible to exclude excess risk of 20% for spontaneous abortion, low birth weight, and congenital malformations.